2006
DOI: 10.1194/jlr.m500430-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bile acid biosynthesis by hepatocyte nuclear factor 4α

Abstract: Hepatocyte nuclear factor 4a (HNF4a) regulates many genes that are preferentially expressed in liver. Mice lacking hepatic expression of HNF4a (HNF4a DL ) exhibited markedly increased levels of serum bile acids (BAs) compared with HNF4a-floxed (HNF4a F/F ) mice. The expression of genes involved in the hydroxylation and side chain b-oxidation of cholesterol, including oxysterol 7a-hydroxylase, sterol 12a-hydroxylase (CYP8B1), and sterol carrier protein x, was markedly decreased in HNF4a DL mice. Cholesterol 7a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 56 publications
(58 reference statements)
7
97
1
3
Order By: Relevance
“…2A). Similar trends were observed for SHP, HNF4a, and Pol II recruitment to the Cyp8b1 promoter region [which harbors the HNF4a response element (Inoue et al, 2006)] (Fig. 2B).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…2A). Similar trends were observed for SHP, HNF4a, and Pol II recruitment to the Cyp8b1 promoter region [which harbors the HNF4a response element (Inoue et al, 2006)] (Fig. 2B).…”
Section: Resultssupporting
confidence: 62%
“…To determine whether GW4064 alters CYP2D6 expression and activity in vivo, GW4064 or vehicle control was intraperitoneally administered to Tg-CYP2D6 mice for 5 days, and hepatic CYP2D6 mRNA and protein levels were measured by qRT-PCR and Western blot, respectively. Cyp8b1, a gene known to be downregulated by SHP (Inoue et al, 2006), was used as a positive control. The results showed that GW4064 significantly decreased both mRNA and protein expression levels of CYP2D6 by ;2-fold ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rescued embryos fail to express the correct profile of liver-specific genes, indicating an additional role for HNF-4␣ in the terminal differentiation of hepatocytes (17). In the adult mouse, Hnf4a expression has been reported in liver, kidney, intestine, stomach, and pancreas (12,13), where HNF-4␣ is responsible for the regulation of genes involved in processes such as insulin secretion (11), gluconeogenesis (18), bile acid synthesis (19), and lipid metabolism in adult humans (20).…”
mentioning
confidence: 99%
“…A human genetic deficiency in HNF4α expression in pancreatic β-cells causes the disease MODY-1 (maturity onset diabetes of the young-1). In adult liver, HNF4α regulates transcription of a large number of genes involved in liver-specific functions, such as bile acid and apolipoprotein synthesis, coagulation, urea synthesis, drug metabolism and gluconeogenesis [6][7][8][9][10][11]. The absence of HNF4α expression in adult mice results in increased mortality [6], thus indicating that HNF4α controls constitutive expression of genes that are essential for liver function.…”
Section: Hnf4αmentioning
confidence: 99%